Ten Tips and Tricks for Performing Alcohol Septal Ablation in Patients with Hypertrophic Obstructive Cardiomyopathy - Veselka, Josef (The International journal of angiology, 2020)
Alcohol septal ablation (ASA) is an effective interventional therapeutic strategy to reduce or eliminate left ventricular outflow tract obstruction in patients with hypertrophic obstructive cardiomyopathy (HOCM). Although ASA was introduced 25 years ago, there are still no available guidelines to follow. Therefore, most interventional cardiologists rely on their own experience, which is often limited by a relatively low number of performed procedures. This paper presents ten tips and tricks to safe and effective ASA for HOCM.
Keywords: hypertrophic obstructive cardiomyopathy; tips and tricks; obstruction; survival